In praise of the stepmother - Vargas Llosa, Mario 1936- (New York, NY Picador USA, 2002)
With meticulous observation and the seductive skill of a great storyteller, Vargas Llosa lures the reader into the shadow of perversion that, little by little, darkens the extraordinary happiness and harmony of his characters. The mysterious nature of happiness and above all, the corrupting power of innocence are the themes that underlie these pages, and the author has perfectly met the demands of the erotic novel, never dimming for an instant the fine poetic polish of his writing.
Translation of: Elogio de la madrastra.